The Dynamics of the Relationship between Attention Deficit Hyperactivity Disorder and Alcohol Use Disorder - Acar, Sevda; Aktaş, Yeliz (Addicta: The Turkish Journal on Addictions, 2024)
Attention-deficit hyperactivity disorder is defined as a neurodevelopmental disorder that begins in child- hood and persists into adulthood. The use of alcohol and substances is a significant risk factor for adults diagnosed with attention-deficit hyperactivity disorder. The majority of research has demonstrated a high prevalence of attention-deficit hyperactivity disorder symptoms among individuals with alcohol use disorder. The literature examines the relationship between attention-deficit hyperactivity disorder and alcohol use disorder from various perspectives, including genetic, neurobiological, behavioral, and psychosocial factors. Individuals diagnosed with attention-deficit hyperactivity disorder are recognized to be at an increased risk of developing alcohol use disorder, particularly due to challenges related to impulsivity and emotion regula- tion. Furthermore, environmental influences, such as family dynamics, along with psychosocial elements like traumatic experiences, also emerge as risk factors for both disorders.The complex relationship between attention-deficit hyperactivity disorder and alcohol use disorder requires a holistic approach to address both conditions properly. In this context, a multimodal strategy that inte- grates addiction treatment with mental health support is essential. Combining pharmacological and non- pharmacological interventions is crucial for enhancing patients’ quality of life and alleviating the impact of comorbid conditions. Early diagnosis and intervention play a pivotal role in the effective management of these disorders.Consequently, a comprehensive understanding of both diagnoses, along with an awareness of their interac- tions, is important for developing effective treatment strategies and interventions.
Keywords: Addiction to alcohol; adult ADHD; alcohol use disorder; attention deficit hyperactivity disorder; emotional regulation; impulsivity